Impact of ICT on privacy and personal data protection in two Malaysian academic libraries - Mohd Roni, Nurul Azurah; Hassan, Basri; Mohd Napiah, Mohd Kamal (2011)
The rapid advance of information and communication technologies (ICT) has permitted the creation of digital libraries. However, the development of the digital library has created certain threats in some aspects especially in terms of privacy and personal data protection which is generally regarded as confidential between the library and the individual. This study aims to investigate the policies, preparedness and awareness of two Malaysian public academic libraries i.e. International Islamic University Malaysia (IIUM) and Universiti Putra Malaysia (UPM) on the issues of privacy and data protection.